Scrapbooking the Everyday Scaffolding of Sexual Violence: Making Sense of ‘Rape Culture’ - WALLING-WEFELMEYER, ROSA,GABRIELA (2022)
Feminist attention to the cultural causes of sexual violence has assumed many forms and debates, with the concept of ‘rape culture’ taking hold in the 1970s and being reinvigorated today. This thesis explores these debates to arrive at its unique conceptualisation of the ‘everyday scaffolding’ of sexual violence. Everyday scaffolding refers to the discursive practices – situated and material ways in which knowledges are formed – through which sexual violence becomes possible and intelligible. Designing an innovative research practice of scrapbooking, this thesis establishes these scaffolds in the lives of its participant scrapbookers; twenty-three adults with unwanted sexual experiences and one UK Rape Crisis centre. Scrapbooking involves saving, organising and sharing ‘scraps’ from everyday life, a potentially enjoyable, therapeutic and consciousness-raising practice. Paying attention to queer, post-structuralist and feminist new materialist thinkers, this research organises scraps from participants’ books and relevant literatures into four scaffolds. Firstly, ‘Conflation and Marginalisation’: where the bringing together and confusing of often contentious sexual matters naturalises and obscures sexual violence, as does the drawing of different boundaries to separate sexual violence out. Secondly, ‘Spectacularisation’: discursive practices by which sexual violence is constituted as a spectacle, a dramatic event cut out from everyday life, with particular audiences in mind. Thirdly, ‘Catching Out’: discursive practices which establish a ‘truth’ beneath a ‘lie’ in need of unmasking, connecting sexual violence to all manner of ‘corrective’ activities. Finally, ‘Weaponisation’: sexual violence as a means towards particular and harmful ends; to further divisive politics, to facilitate sexual access, and to naturalise ‘vulnerability’. These four scaffolds are presented in order to both name and change sexual violence in ways which work with the ambiguity and potentiality of the everyday, the necessity for continuum-thinking and the reality of the research’s own performative involvement in the worlds or ‘rape cultures’ it claims to make sense of